THE ROLE OF PUBLIC SERVICE ADVERTISING AS SOCIAL MARKETING COMMUNICATION IN THE TRI HITA KARANA ANIMATED VIDEO NON-COMMERCIAL CAMPAIGN - Ni Putu Sinta Dewi; I Nyoman Miyarta Yasa; Muhammad Fathoni; I Gede Anjas Kharisma Nata (RADJA PUBLIKA, 2025)
This study examines the role of public service announcements as a non-commercial campaign medium with a focus on Tri Hita Karana animated videos. The purpose of this study is to analyze the role of public service announcements as a campaign medium in social marketing communications and to examine the implementation of persuasive communication processes contained in animated videos that represent the philosophical values ​​contained in Tri Hita Karana. The method used in this study is a descriptive qualitative approach, involving a review of documentation and a literature search. The results of the study indicate that public service announcements, as a non-commercial campaign medium, can be an effective strategy for conveying educational messages, increasing public awareness, and encouraging behavioral change. Non-commercial campaigns align with the principles of social marketing, which, in their implementation, aim to promote social values. The implementation of AIDDA (Attention, Interest, Desire, Decision, Action) in animated videos through visual messages, simple narratives that foster interest, delivery of visual narratives about the benefits of harmonious living, and invitations to encourage positive decisions in accordance with the values ​​of Tri Hita Karana. This study contributes to strengthening the understanding of the implementation of persuasive communication processes in Tri Hita Karana animated campaign videos as a strategic communication instrument relevant to social development.